Upaya Meningkatkan Pemahaman Sains Melalui Metode Eksperimen pada Anak Usia 5-6 Tahun di RA Az Zahra Cangkrep Lor - Fairus Suryani Munir; Anna Safitri (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Children's understanding of science at RA Az Zahra is still very low, children are less active and feel less active bored and still having difficulty understanding science activities. This condition is caused by use the method used is not appropriate. The aim of the researcher in conducting this research is to know Children's understanding of science increases through the use of experimental methods. Researcher using a type of classroom action research (PTK). In this study took 10 girls aged 5-6 years as research subjects. Researcher using data collection techniques in the form of observation, performance and documentation. Results Action research can be seen in observing children's development in each cycle, namely pre-cycle with a score of 30%, a percentage of 50% in the first cycle stage and a percentage of 80% in cycle II stage. Percentage increase in understanding of science through experimental methods has achieved a success indicator of 80%. So that is the conclusion of this research proves that the experimental method has been proven to be able to increase understanding science in children aged 5-6 years. This can be seen from cycle II which reached an indicator of 80%.